Konsep Pendidikan Anak Dalam Perspektif Islam dan Barat (Studi Komparasi Pemikiran Imam Al-Ghazali dan Jean Jacques Rousseau) - Nisa', Mas Ayu Ainun; Bakar, M. Yunus Abu (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This study aims to examine in depth and compare the concept of children's education according to two great figures from two different intellectual traditions, namely Imam Al-Ghazali as a classical Islamic thinker and Jean-Jacques Rousseau as a philosopher from the modern Western world. Al-Ghazali emphasized that children's education should be oriented towards the formation of a whole human being, not only through intellectual development, but also through the spiritual and moral dimensions. According to him, the focus of education lies in the cultivation of faith, the development of noble morals, and self-control through exemplary methods, positive habituation, advice, supervision, and motivation. Rather, Rousseau viewed education as a natural process that leads children to grow according to their nature, by providing space for freedom, hands-on experience, and the development of independence without excessive intervention. This research uses a qualitative approach with the library research method, through the analysis of primary and secondary works of both figures. The results of the study show that although both depart from different civilization contexts and philosophical paradigms, there is a common view in viewing children as individuals who have natural potential that must be appreciated and developed gradually. Furthermore, the study found that Al-Ghazali and Rousseau's thinking could be integrated to form a holistic paradigm of children's education. The integration results in an approach that balances cognitive, affective, spiritual, and moral aspects, making it relevant to be applied in a contemporary education system oriented towards character formation and humanity.